PEMIKIRAN NURCHOLIS MADJID (CAK NUR) MENUJU MASYARAKAT MADANI DI INDONESIA - Mappisona, Andi; Natsif, Fadli Andi; Laman, Ilham (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2025)
This study aims to analyze Nurcholish Madjid’s (Cak Nur) concept of masyarakat madani (civil society), describe its main principles and characteristics, and assess its relevance to promoting a democratic, tolerant, and just social order in Indonesia. The research problem focuses on how Cak Nur defines masyarakat madani as a civilized society grounded in public ethics (civility), and to what extent this framework addresses Indonesia’s contemporary socio-political challenges. The study employs normative theological and normative juridical approaches within a library research design. Data were collected through documentary analysis of Cak Nur’s writings, scholarly literature, and relevant statutory regulations, and were examined using qualitative descriptive-analytical methods. The findings show that Cak Nur’s masyarakat madani draws inspiration from the historical example of Medina, emphasizing plural coexistence, justice, deliberation, and respect for differences. Its key characteristics include pluralism, tolerance, freedom of expression and association, the rule of law, equal justice, and Islamic brotherhood compatible with social diversity. The study concludes that this concept remains highly relevant as a normative and corrective framework to strengthen substantive democracy, human rights protection, and accountable governance in Indonesia.